Sparse Subspace Clustering via Group Sparse Coding - Budhaditya, S.; Pham, DucSon; Phung, D.; Venkatesh, S. (SIAM, 2013)
We propose in this paper a novel sparse subspace clustering method that regularizes sparse subspace representation by exploiting the structural sharing between tasks and data points via group sparse coding. We derive simple, provably convergent, and computationally efificient algorithms for solving the proposed group formulations. We demonstrate the advantage of the framework on three challenging benchmark datasets ranging from medical record data to image and text clustering and show that they consistently outperform rival methods.